MEDICINAL BIOMAGNETISM FOR ANALGESIA - APPLICATION OF STATIC MAGNETIC FIELD THROUGH MODERN TRAUMA PROTOCOL: CROSS-SECTIONAL OBSERVATIONAL STUDY - Palaikis, Claudia; Macêdo, Joseane; Silva Ataides, Valéria; Lúcia Silva, Vera; Mara Rambo Martini, Angela; Viapiana Bossa, Adriane; Souza Santos, Jefferson (Health and Society, 2023)
Pain is one of the most common reasons people seek medical care and is related to most disease states. It is estimated that the prevalence of pain varies from 37% to 70%, generating functional limitations and negative impacts on quality of life. Medicinal Biomagnetism (MB) is a therapeutic approach that corrects bioelectromagnetic dysfunctions through the application of Static Magnetic Fields (SMF), acting on the most varied pathological states. SMF can be applied in a controlled manner, locally to specific parts of the human body, aiming to improve inflammatory, infectious and dysfunctional conditions that can lead to pain. Objective: To evaluate the analgesic effects of applying one of the MB protocols, the Modern Trauma Pair (MTP), in participants with pain. Methodology: A cross-sectional observational study was carried out, where the MTP was applied to 30 participants who had some type of pain, using the Visual Analogue Scale, to assess the intensity of subjective pain. Results: A statistically significant difference (p<0.001) was observed between the times before applying the protocol (average of 6.87), and 15 minutes after applying the MTP. There was a progressive decline in reported pain perception, reaching an average of 4.74 for acute pain and 4.84 for chronic pain, after 60 minutes of use. Conclusion: MTP can be an important therapeutic approach for pain relief. The Medicinal Biomagnetism protocol, MTP can contribute quickly and with minimal side effects to analgesia in different types of pain.